Comparison of massage and prone position on heart rate and blood oxygen saturation level in preterm neonates hospitalized in neonatal intensive care unit: A randomized controlled trial - Azamolmolouk Elsagh; Razieh Lotfi; Siamak Amiri; Haleh Hatam Gooya (Wolters Kluwer Medknow Publications, 2019)
Background: These days, most of the admitted infants in neonatal intensive care units (NICU) are premature infants. Infant massage and prone position has been recommended for several decades to have a positive effect on preterm and low birth weight infants. The objective of this study was to determine the effects of neonatal massage with prone positioning in preterm infants on Heart Rate (HR), and Oxygen Saturation (O2Sa) status. Materials and Methods: This is a controlled randomized three-group clinical trial study conducted on hospitalized infants in selected hospitals of Alborz University of Medical Sciences in Karaj-Iran. There are about 75 preterm infants (33-37 weeks) who met inclusion criteria were randomly assigned to groups of position, massage as intervention groups, and a control group. Intervention (prone position and massage) was administrated for five straight days. The repeated measure ANOVA test was performed to evaluate and compare the effect of interventions.p value less than 0.05 was considered as statistical significance. Results: The Repeated Measure two-way Analysis of Variance (RM-ANOVA) result showed a significant difference in HR and SaO2 in different time points among control, position and massage groups with RM-ANOVA (F10,360=10.376,p < 0.001). HR values was reduced and SaO2 values was increased in intervention groups with RM-ANOVA (F5,360=2.323,p < 0.001). Conclusions: Results showed that massage and prone position equally led to the reduction of HR and increase of SaO2, compared to control group.